Expression, characterisation and homology modelling of a novel hormone-sensitive lipase (HSL)-like esterase from Glaciozyma antarctica - Mohamad Tahir, Hiryahafira; Raja Abdul Rahman, Raja Noor Zaliha; Leow, Adam Thean Chor; Mohamad Ali, Mohd Shukuri (MDPI, 2020)
Microorganisms, especially those that survive in extremely cold places such as Antarctica, have gained research attention since they produce a unique feature of the protein, such as being able to withstand at extreme temperature, salinity, and pressure, that make them desired for biotechnological application. Here, we report the first hormone-sensitive lipase (HSL)-like esterase from a Glaciozyma species, a psychrophilic yeast designated as GlaEst12-like esterase. In this study, the putative lipolytic enzyme was cloned, expressed in E. coli, purified, and characterised for its biochemical properties. Protein sequences analysis showed that GlaEst12 shared about 30% sequence identity with chain A of the bacterial hormone-sensitive lipase of E40. It belongs to the H group since it has the conserved motifs of Histidine-Glycine-Glycine-Glycine (HGGG)and Glycine-Aspartate-Serine-Alanine-Glycine (GDSAG) at the amino acid sequences. The recombinant GlaEst12 was successfully purified via one-step Ni-Sepharose affinity chromatography. Interestingly, GlaEst12 showed unusual properties with other enzymes from psychrophilic origin since it showed an optimal temperature ranged between 50–60 °C and was stable at alkaline pH conditions. Unlike other HSL-like esterase, this esterase showed higher activity towards medium-chain ester substrates rather than shorter chain ester. The 3D structure of GlaEst12, predicted by homology modelling using Robetta software, showed a secondary structure composed of mainly α/β hydrolase fold, with the catalytic residues being found at Ser232, Glu341, and His371.